2015
DOI: 10.1536/ihj.14-246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Left Ventricular Hypertrophy and Their Cutoffs in Peritoneal Dialysis Patients

Abstract: SummaryCardiovascular complications are the main cause of morbidity and mortality in peritoneal dialysis (PD) patients. Left ventricular hypertrophy (LVH) is a major predictor of the development of cardiovascular events. This study aimed to identify risk factors that contribute to the development of LVH and to determine their cutoffs in patients on maintenance peritoneal dialysis.In this cross sectional study we evaluated the association of 23 variables including age, PD vintage, ultrafiltration, urine volume,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Other potential mechanisms connecting renal function to OSA relate to upper airway patency, which may be compromised in the setting of uremic myopathy [14, 15]. As more studies emerge linking decreased residual renal function to increased cardiovascular risk in ESRD and increased residual renal function to prolonged survival, this association with OSA is intriguing given that OSA has similarly been found to predict increased cardiovascular morbidity and mortality [1618]. …”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms connecting renal function to OSA relate to upper airway patency, which may be compromised in the setting of uremic myopathy [14, 15]. As more studies emerge linking decreased residual renal function to increased cardiovascular risk in ESRD and increased residual renal function to prolonged survival, this association with OSA is intriguing given that OSA has similarly been found to predict increased cardiovascular morbidity and mortality [1618]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that underlie SCD in dialysis patients are complicated, and many factors have been suggested to explain the increased arrhythmic risk in patients on dialysis. Left ventricular hypertrophy, which is a common echocardiographic finding in dialysis patients, 39) has been linked to an increased risk of SCD as an arrhythmogenic substrate in CKD. Metabolic and electrolyte abnormalities, as well as fluid overload, may promote arrhythmias and increase the risk of SCD.…”
mentioning
confidence: 99%
“…For analysis, patients were categorized to two groups according to PGLI ≤3 g/kg per day and PGLI >3 g/kg per day. The cut‐off of 3 g/kg per day is based in our previous studies that evaluated the impact of PGLI on hydration status, inflammation and left ventricular mass in stable patients on maintenance PD . These studies demonstrated that hemoglobin A1c (HbA1c), fluid overload, plasma high sensitivity C‐reactive protein (hsCRP) and interleukin (IL)‐6 levels were significantly higher in patients with PGLI >3 g/kg per day compared with those with PGLI ≤3 g/kg per day ; PGLI was positively correlated with HbA1c and left ventricular mass index ( P < 0.001) and patients with PGLI >3 g/kg per day had higher HbA1c and left ventricular mass index compared to those with PGLI ≤3 g/kg per day ( P < 0.001) ; PGLI seemed to be possible predictor of left ventricular hypertrophy and its cutoff that was associated with the presence of LVH was 3.2 g/kg per day ; and finally, low peritoneal glucose load was associated with a protective effect from the development of left ventricular hypertrophy in PD patients .…”
Section: Methodsmentioning
confidence: 99%